The Design of an Android-Based Integrated Islamic Boarding School Information System as an Impact of Covid-19 - Syauqie Muhammad Marier; Anis Susila Abadi (Telematika, 2021)
Purpose: This study aims so that all information that is spread through various information systems in Islamic boarding schools can be known through an integrated systemDesign/methodology/approach: The method of developing the system using the prototype methodFindings/result: Android-based integrated information systemOriginality/value/state of the art: System integration in Islamic boarding schools that is carried out is the integration process of various systems that previously existed